Institutional arrangements and economic analysis of the management of livestock water infrastructure investments in agro-pastoral areas of Teso and Karamoja in Uganda - Aseete, Paul; Ilukor, John; Bagamba, Fredrick; Lwiza, Florence; Walusimbi, Sadhat; Ng’andwe, Pushina Kunda; Oryokot, Joseph; Ndamira, Barbara Magezi; Sebudde, Rachel K. (Frontiers Media S.A, 2024)
The study aimed to evaluate the utilization, management structures, costs, and benefits of livestock water infrastructure in the pastoral communities of the Teso and Karamoja sub-regions. Data were collected on various water infrastructures, including boreholes, valley dams, and valley tanks. The findings suggest that investing in water infrastructure is economically viable, although functionality and usage differ across regions. Water use associations (WUAs) and community volunteers predominantly managed the water infrastructure, with local governments providing oversight. In Teso, 45%–75% of water use associations were deemed functional, compared to a lower rate of 33%–40% in Karamoja. Generally, users of water infrastructure in Teso demonstrated a higher willingness to pay for various services compared to those in Karamoja. The study also found that, under the status quo, co-management and joint efforts between WUAs and volunteers could be more economically viable management structures for boreholes. Valley dams could be better managed by WUAs, while local governments, with community support, could effectively manage valley tanks. The major challenges in managing water facilities included free riding, failure to enforce regulations, the potential for ownership tragedy, inadequacies in managing technologies, and the effects of drought. The research and implications of these findings are further discussed in the study.